Faktor Risiko Kejadian MalariaPada Balita - Oktafianus Radja Tuka; Nurdina Nurdina; Novita Anna; Indasah Indasah; Agustin Widyowati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Malaria can cause a decrease in productivity because malaria in toddlers can interfere with the growth and development of infants and toddlers.The province of NTT is the province with the third highest incidence and prevalence of malaria (6.8% and 23.3%) after the provinces of Papua and West Papua with incidence and prevalence (9.8% and 28.6%). The aim of the study was to analyze the influence of risk factors on the incidence of malaria in toddlers in the working area of the Ledeunu Health Center, Sabu Raijua Regency.This made the researchers want to find out what factors influenced the incidence of malaria in toddlers, one of which was at the Ledeunu Public Health Center, Sabu Regency. Therefore, in this study, researchers will analyze the effect of the knowledge of mothers under five, the use of mosquito nets, the use of mosquito poison, the presence of wire netting, the construction of house walls and the behavior and presence of livestock pens on the incidence of malaria. Malaria can cause a decrease in productivity because malaria in toddlers can interfere with the growth and development of infants and toddlers.The province of NTT is the province with the third highest incidence and prevalence of malaria (6.8% and 23.3%) after the provinces of Papua and West Papua with incidence and prevalence (9.8% and 28.6%). The aim of the study was to analyze the influence of risk factors on the incidence of malaria in toddlers in the working area of the Ledeunu Health Center, Sabu Raijua Regency.This made the researchers want to find out what factors influenced the incidence of malaria in toddlers, one of which was at the Ledeunu Public Health Center, Sabu Regency. Therefore, in this study, researchers will analyze the effect of the knowledge of mothers under five, the use of mosquito nets, the use of mosquito poison, the presence of wire netting, the construction of house walls and the behavior and presence of livestock pens on the incidence of malaria. Based on the results of the analysis of bivariate analysis of the risk factors of knowledge of mothers under five (OR = 2.6 , 95%Cl=1.246 -5.348), use of mosquito nets (OR= 2,8, 95% Cl = 1.481-5.402), Use of wire gauze (OR=0,39, 95%Cl= 0.188-0.823),construction of house walls (OR= 2,3, 95%Cl= 1 .226-4.546), mosquito poison ( OR = 0.47, 9 5 % C l = 0.248-0.906), and presence of cage (OR=1,2, 95% Cl=0.690-2.390). From the multivariate analysis, it was found that the risk factors that influence the incidence of malaria are: use of mosquito nets, construction of house walls and use of mosquito poison. The most dominant factor is the use of mosquito nets p = 0.001 Confidence Interval (CI) 9 5%=1.481-5.402. Based on the results of the analysis, it can be seen that the use of mosquito nets, the construction of house walls, and mosquito poisons has a probability/possibility of being at risk of contracting malaria by 97%.